Heavy Metals Their Environmental Impacts and Mitigation - Khaled Nazal, Mazen; Zhao, Hongbo (IntechOpen, 2021)
In recent years, urbanization and industrialization have produced large amounts of heavy metals, which are highly toxic to both humans and the environment. This book presents a comprehensive overview of heavy metals including their physiochemical properties, toxicity, transfer in the environment, legislation, environmental impacts, and mitigation measures. Written by experts in the field, chapters include scientific research as well as case studies.